Synthesis, Structure, and Properties of Quinone Methides Incorporating Thiophene and Bithiophene Derivatives: New Overcrowded Extended Quinonoid π-Systems - Kurata, Hiroyuki; Inoue, Taihei; Suzuki, Takeshi; Hirao, Yasukazu; Matsumoto, Kouzou; Kubo, Takashi (Synlett, 2016)
The title compounds were synthesized through multiple Suzuki–Miyaura couplings followed by oxidation, and their structures and properties are described. They show large conformational changes and three color change upon electronic reduction.
Keywords: quinone methide; thiophene; nonplanar π-system; redox system; electrochromism; Suzuki–Miyaura coupling